Climate Change Policies and Challenges in Indonesia - Kaneko, Shinji; Kawanishi, Masato (Springer Japan : Imprint: Springer, 2016)
This book demonstrates the challenges and opportunities of climate change actions in developing countries and primarily focuses on case studies in Indonesia, the world's fourth most populous country. The most important feature of the book is its examination of multiple facets of climate change issues in Indonesia, which allows readers to understand the complexity of climate change in developing countries: the synergies and trade-offs between different climate change actions as well as between climate and development priorities. Another unique feature is that it was jointly written by Indonesian and international authors, as well as by academics and development practitioners. This book addresses questions concerning mitigation measures in major sectors with original analyses of aspects including energy subsidies, sectoral energy efficiencies in manufacturing sectors, forest concessions, energy-saving labeling schemes, policy mixes for the urban transportation sector, and the introduction of waste-to-energy technologies. The book provides first-hand knowledge and data on energy and the institutional realities in Indonesia, which are not widely and readily available to an international audience. It offers a valuable reference guide for professionals working for governments and NGOs and donor agencies in the fields of climate change and development in developing countries. This work is also a valuable resource for undergraduate and graduate students of economics and environmental and development studies, in particular those who are interested in the synergies and conflicts between climate change and development. .